(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess knowledge and attitudes toward gender diversity and sexual orientation among students at Thai Nguyen University of Medicine and Pharmacy and identify related factors. Subjects and methods: A cross-sectional descriptive study was conducted among 874 medical students from the first to the fifth academic year using stratified sampling by year of study. Data were collected using a self-administered questionnaire including demographic information, 20 knowledge questions, and 15 attitude questions measured on a Likert scale. Results: The mean knowledge score regarding gender diversity and sexual orientation was 15.3 ± 2.8 out of 20 points; 68.2% of students demonstrated adequate knowledge. The mean attitude score was 52.0 ± 9.3 out of 75, and the proportion of students with positive attitudes toward the LGBT community was 32.2%. Most students agreed that LGBT individuals should receive equal healthcare and that healthcare workers have a responsibility to provide non-discriminatory care to LGBT patients. Female students had significantly higher rates of correct knowledge and positive attitudes than male students (p < 0.05). Students who had not yet participated in clinical practice showed better knowledge and more positive attitudes than those who had completed clinical rotations (p < 0.001). Students with adequate knowledge had a significantly higher rate of positive attitudes compared to those with inadequate knowledge (38.4% vs. 18.7%; p < 0.001). Conclusion: Medical students demonstrated relatively good knowledge of gender diversity and sexual orientation; however, positive attitudes toward the LGBT community remained limited. Greater integration of LGBT health content and non-discriminatory care into medical education curricula is needed.